Next generation sequencing of breast implant‐associated anaplastic large cell lymphomas reveals a novel STAT3‐JAK2 fusion among other activating genetic alterations within the JAK‐STAT pathway. Issue 4 (18th February 2021) - Quesada, Andrés E.; Zhang, Yanming; Ptashkin, Ryan; Ho, Caleb; Horwitz, Steven; Benayed, Ryma; Dogan, Ahmet; Arcila, Maria E.
Abstract: Breast implant associated anaplastic large cell lymphoma (BIA‐ALCL) is a distinct type of ALCL, and a new provisional entity by the 2016 revision of the World Health Organization (WHO) classification of tumors of hematopoietic and lymphoid tissues. In contrast to systemic and primary cutaneous ALCLs, BIA‐ALCLs have been genetically characterized by the absence of fusions and frequent activation of the JAK ‐ STAT3 pathway through mutations in JAK1 and STAT3 . In this study, we report the results of the genetic profiling of 9 BIA‐ALCL cases supporting the role of the JAK ‐ STAT pathway activation in this entity, including the identification of an activating STAT3 ‐ JAK2 fusion similar to those recently reported in T‐cell lymphoproliferative disorders of the gastrointestinal tract. To our knowledge, this is the first fusion reported in BIA‐ALCL, providing further insight into the overall genetic landscape of this rare entity as well as uncovering potential options for targeted therapy in cases with advanced disease.